ANALISIS KEMAMPUAN LITERASI STATISTIK PESERTA DIDIK DI SEKOLAH DASAR PADA PEMBELAJARAN MATEMATIKA - Wahyuni, Sri; Azminudin Latif; Asri Darwanti; Nining Setyaningsih; Sumardi, Sumardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the statistical literacy skills of students and to understand the difficulties they encounter in solving problems related to statistical concepts. The research employs a qualitative approach with a descriptive method. The subjects of this study are 23 fifth-grade students at SDN 01 Wonokeling, Jatiyoso, Karanganyar. Data collection was carried out using a statistical literacy skills test instrument, covering statistical material. The study reveals that the percentage of students' statistical literacy skills is still low in each indicator. Students' ability to interpret data has the highest percentage at 65%, while their ability to present data has the lowest percentage at 47%. Many students still do not fully understand statistical concepts, which hinders their ability to present data and draw accurate statistical conclusions.